Primary segmental intestinal volvulus associated with acute appendicitis - Emad M. AL-Osail; Naif Alotaibi; Faisal Alghamdi; Majid Alkhamis (Journal of Pediatric Surgery Case Reports, 2018)
Introduction: Segmental intestinal volvulus without underlying causes is called Primary Segmental Volvulus. Herein, we report a rare case of segmental ileal volvulus associated with acute appendicitis. Case Presentation: A 3-year-old boy presented with complaints of diarrhoea associated with vomiting, central abdominal pain, and decreased activity for 2 days. He was referred to paediatric surgery as a case of acute appendicitis. Ultrasound of the abdomen showed acute appendicitis with ileoileal target sign. Laparotomy was done, which showed segmental ileal volvulus without malrotation associated with inflamed appendix and fecolith at the tip. Appendectomy plus intestinal resection and anastomosis were also done. Discussion: Primary Segmental Intestinal Volvulus is a very rare condition, and only a few cases have been reported in the literature. It has a prevalence of 22.9%–26.3% in children.In our case, ultrasound findings are suggestive of acute appendicitis and suspicion of intussusception. Intraoperatively, segmental intestinal volvulus was observed along with inflamed appendix and a fecolith at its tip. Conclusion: Primary Segmental Intestinal Volvulus should be considered as a differential diagnosis of any child patient who came with small bowel obstruction symptom. Keywords: Segmental intestinal volvulus, Malrotation, Fecolith, Acute appendicitis, Case report